Major trends in public sector innovation: a bibliometric analysis - Saharah Sapiyi; Nur Riza Mohd Suradi; Zainol Mustafa (Penerbit Universiti Kebangsaan Malaysia, 2024)
It is well known that innovation plays a substantial role in the public sector. However, there are concerns about how far public sector innovation (PSI) research has contributed in providing ideas to the government in formulating and implementing public policy. This study intends to investigate how PSI research has progressed and been disseminated, explore major topics mentioned in PSI studies and determine the primary players in PSI studies. This research analysed the bibliometrics of scholarly publications on public sector innovation as of August 2021, as documented in the Scopus database. We analysed the evolution of PSI research in 53 years by assessing published studies, source titles, types of sources and documents, as well as the languages in which the papers have been published. We additionally analysed PSI’s main research topics by examining popular subject categories, the most often used keywords and title analysis. Finally, we investigated the key actors in PSI research by focusing at the biggest contributions nations to PSI studies, the major establishments involved, as well as authorship and citation analysis. The conclusions suggested that during the initial stages of PSI development half a century ago, public sector innovation attracted the interest of Eastern and Western scholars, as well as the number of books and articles published each year which have increased dramatically. Although there has good inter-country cooperation exists, a deficit in PSI research also exists from specific nations compared to the rest of the globe. Our results contribute significantly to public sector innovation inclusiveness.